Teaching physical education creatively - Pickard, Angela; Maude, Patricia (Routledge, 2014)
"Teaching Physical Education Creatively provides knowledge and understanding in order to engage creatively with the primary Physical Education curriculum for both trainee teachers and qualified teachers. It is full of ideas for developing the teaching of dance, games gymnastics and outdoor and adventurous activities in an innovative and engaging manner. With an emphasis on developing creative teaching processes by building from children's curiosity, imagination and need to explore and move, it forges clear links between research and practice, and offers suggestions for developing exciting engaging new approaches to teaching physical education. Key topics explored include:Physical Competence and Physical Literacy ; Creative ways to develop the teaching of dance, games, gymnastics and outdoor and adventurous activities ; Developing understanding of space, speed and dynamics ; Creative lesson planning ; Inclusive approaches and aspects of differentiation. Teaching Physical Education Creatively presents the theory and background necessary to develop a comprehensive understanding of creative teaching and children's learning. Packed with practical guidance and inspiration for lively enjoyable physical education it is an invaluable resource for undergraduate and postgraduate students in initial teacher training, practicing teachers, and undergraduate students of physical education"-- Provided by publisher.